Characteristics and management of skin cancers in very elderly patients: A real‐world challenge for clinicians. Issue 10 (26th June 2022) - Lai, Michela; Pampena, Riccardo; Mirra, Marica; Raucci, Margherita; Benati, Elisa; Borsari, Stefania; Lombardi, Mara; Banzi, Maria; Castagnetti, Fabio; Palmieri, Tamara; Piana, Simonetta; Ramundo, Dafne; et al.
Abstract: The increase life expectancy led to an expected increase in skin cancer incidence in older patients. Their treatment can require a complex decision‐making process. Limited data are available on characteristics, management and outcome of skin tumours in nonagenarian and centenarian patients. The aim of our study was to describe epidemiology, clinical‐pathological features and treatment strategies of skin cancers in a cohort of patients aged ≧95 years. A total of 116 patients ≧95 years of age presented for the evaluation of 225 skin lesions (mean of 1.94 lesions per patient). The mean age was 97.4 years, 57.8% were women. Most patients had an ECOG score of 3 (49.3%) or 4 (32%). Lesions were mainly located on the head and neck area (74.2%), upper (7.1%) and lower (6, 2%) limbs. The majority of patients presented with non‐melanoma skin cancers (183/225; 81.3%), 25/225 (11.1%) had actinic keratosis, 5 (2.2%) melanoma and 2 (0.9%) atypical fibroxanthoma. Forty‐eight lesions (21.3%) were treated with surgery, 58 (25.8%) with radiotherapy. The management of 73 lesion (32.4%) was discussed at the multidisciplinary tumour board meeting. One patient died for the progression of a squamous cell carcinoma; 74 patients died for causes unrelated to skin tumours, 36 are still alive after a mean follow‐up of 27.27 months. This cohort study confirms that age is not per se a contraindication for treatment of skin cancers in elderly patients. Our results support the importance of a patient‐centred care approach that should take into consideration patient's preferences, comorbidities, compliance and possible adverse events.